2011
DOI: 10.1016/j.compedu.2011.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in students’ mathematics game playing

Abstract: The investigation monitored the digital game-playing behaviours of 428 primary-aged students (aged 10-12 years). Chi square analysis revealed that boys tend to spend more time playing digital games than girls while boys and girls play quite different game genres. Subsequent analysis revealed statistically significant gender differences in terms of the types of mathematics-rich games students prefer to play. Girls preferred to play games that required problem solving, quantitative computations and the interpret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 20 publications
(19 reference statements)
0
27
0
1
Order By: Relevance
“…In contrast, female learners display learning anxiety in a competitive game and cannot find pleasure in the process; such negative affectivity affects their learning performance. Lowrie and Jorgensen (2011) also found that women tend to have a lower learning achievement than men in digital games of a competitive nature. This study showed that there was no significant difference in the correlation in the achievement goals between genders, representing a different result from the aforementioned two studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, female learners display learning anxiety in a competitive game and cannot find pleasure in the process; such negative affectivity affects their learning performance. Lowrie and Jorgensen (2011) also found that women tend to have a lower learning achievement than men in digital games of a competitive nature. This study showed that there was no significant difference in the correlation in the achievement goals between genders, representing a different result from the aforementioned two studies.…”
Section: Discussionmentioning
confidence: 99%
“…This positive affectivity allows men to reach higher learning achievements from playing MMORPGs. Lowrie and Jorgensen (2011) showed that the level of cognitive perception differed by genders plays a role in the attitude towards digital game-based learning, and learning attitude is correlated to learning achievements.…”
Section: Gender and Digital Game-based Learningmentioning
confidence: 99%
“…When designing a game, information on how a specific population plays a game, and their learning strategies, could mark a milestone in the way the game is developed to better fit the preferences of its target audience. Many researchers pointed out how gender differences do affect the effectiveness in game learning (Chou & Tsai, 2007;Lowrie & Jorgensen, 2011;Papastergiou & Solomonidou, 2005). However, recent studies put the spotlight in a different place: the broad play-style (such as "casual" or "hardcore") of players can explain those differences better than their gender does (Manero, Torrente, Fernández-Vara, & Fernández-Manjón, n.d.).…”
Section: Usage Scenariosmentioning
confidence: 99%
“…In particular, several researchers have emphasized the importance of investigating gender differences in e-learning studies in recent years (Hung, Hwang, Lee, & Su, 2012;Lowrie & Jorgensen, 2011;Tomte & Hatlevik, 2011;Yang & Chen, 2010).…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%